Pedalling downhill and freewheeling up; a penguin perspective on foraging - Rory Wilson (Aquatic Biology, 2010)
Wilson, R. P., Shepard, E. L. C., Gomez-Laich, A., Frere, E., Quintana, F. (2010). Pedalling downhill and freewheeling up; a penguin perspective on foraging. Aq. Biol. 8: 193-202.